Elements of Natural Logic for the Study of Unnoticed Misunderstanding in a Communicative Approach to Learning - Kohler, Alaric (My University, 2017)
This paper presents a methodology building on Grize’s Natural Logic to study unnoticed misunderstanding in teaching and learning communication. The study of unnoticed misunderstanding is important for education, as misunderstanding has been pointed out as a candidate mechanism for the reproduction of social inequalities at school. It is also a challenge, because most linguistic approaches rely on the interlocutors’ attempts to repair a specific communicative failure for identifying and describing misunderstanding. Additionally, the study of misunderstanding at school requires not only a discursive but also a cognitive approach to understanding, in order to relate the description of misunderstanding to the school subject matter. We present one example of misunderstanding at college, in physics, to illustrate the methodology. I argue that Natural Logic provides a useful theory for relating a communicative level of analysis with a semiotic level, allowing a scientific study of interlocutors’ interpretation here and now.
Keywords: Natural Logic situation of misunderstanding learning communication communicative faillure